2016
DOI: 10.2298/vsp140909034t
|View full text |Cite
|
Sign up to set email alerts
|

Choice of root canal irrigants by Serbian dental practitioners

Abstract: This study shows significant changes in the irrigation protocol applied in Serbian dental community. After 3 years of observation, NaOCl became widely accepted as the irrigant of choice, whereas H2O2 lost its popularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…But in their survey they established that in general 3% sodium hypochlorite is the most frequently used irrigant. Tosic et al 7 in a survey performed in Serbia reported that the…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…But in their survey they established that in general 3% sodium hypochlorite is the most frequently used irrigant. Tosic et al 7 in a survey performed in Serbia reported that the…”
Section: Discussionmentioning
confidence: 97%
“…This was the result from their first survey. After a second survey (3 years later) NaOCl became the most popular irrigant in all groups and increased use of Chlorhexidine especially in the first group comprising young dentists 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium hypochlorite is the most commonly used endodontic irrigant worldwide and continues to be favoured as it remains the only material capable of dissolving organic tissue within the root canal system. 10,[12][13][14][15][16][17] Although NaOCl is regarded as safe for endodontic use, the cytotoxic results of mishaps and/or accidents must be highlighted. It is essential that clinicians are trained, and remain skilled and equipped, to deal immediately and effectively with any repercussions of a NaOCl accident.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire (Table 1) was made up of 20 questions with multiple-choice answers covering all the aspects of irrigation protocol in endodontics, including the variables which are not covered in previous surveys (Table 2). 1,[9][10][11][12][13][14][15][16][17][18][19] A total of 150 dental clinics were personally visited and questionnaire form was given by hand. Among them 144 forms were completely filled and successfully collected, obtaining a response rate of 96%.…”
Section: Methodsmentioning
confidence: 99%